Virulence traits and novel drug delivery strategies for mucormycosis post-COVID-19: a comprehensive review - Faiyazuddin, Md.; Sophia, A.; Ashique, Sumel; Gholap, Amol D.; Gowri, S.; Mohanto, Sourav; Karthikeyan, C.; Nag, Sagnik; Hussain, Arif; Akhtar, Mohammad Shabib; Bakht, Md. Afroz; Ahmed, Mohammed Gulzar; et al. (Frontiers in Immunology, 2023)
The outbreak of a fatal black fungus infection after the resurgence of the cadaverous COVID-19 has exhorted scientists worldwide to develop a nutshell by repurposing or designing new formulations to address the crisis. Patients expressing COVID-19 are more susceptible to Mucormycosis (MCR) and thus fall easy prey to decease accounting for this global threat. Their mortality rates range around 32-70% depending on the organs affected and grow even higher despite the treatment. The many contemporary recommendations strongly advise using liposomal amphotericin B and surgery as firstline therapy whenever practicable. MCR is a dangerous infection that requires an antifungal drug administration on appropriate prescription, typically one of the following: Amphotericin B, Posaconazole, or Isavuconazole since the fungi that cause MCR are resistant to other medications like fluconazole, voriconazole, and echinocandins. Amphotericin B and Posaconazole are administered through veins (intravenously), and isavuconazole by mouth (orally). From last several years so many compounds are developed against invasive fungal disease but only few of them are able to induce effective treatment against the micorals. Adjuvant medicines, more particularly, are difficult to assess without prospective randomized controlled investigations, which are challenging to conduct given the lower incidence and higher mortality from Mucormycosis. The present analysis provides insight into pathogenesis, epidemiology, clinical manifestations, underlying fungal virulence, and growth mechanisms. In addition, current therapy for MCR in Post Covid-19 individuals includes conventional and novel nano-based advanced management systems for procuring against deadly fungal infection. The study urges involving nanomedicine to prevent fungal growth at the commencement of infection, delay the progression, and mitigate fatality risk.